TO COMPARE THE INFLATION HEDGING CAPABILITIES ACROSS THE JSE INDUSTRY STOCK RETURNS WHILE ACCOUNTING FOR INVESTOR SENTIMENT AND INTEREST RATES - Naidoo, Deevarshan; Moores-Pitt, Peter; Muzindutsi, Paul-Francios (Jurnal Bisnis dan Keuangan, 2025)
Rising energy and food prices, driven by the Russian-Ukrainian conflict, have pushed inflation to its highest levels in decades, exacerbated by supply chain disruptions stemming from the COVID-19 pandemic. In this context, diversifying investment portfolios to include assets that hedge against inflation is increasingly important. This study analysed South African data from 2007 to 2024, using ARDL and NARDL models, to examine the inflation-hedging capabilities of 10 sectoral stocks and the JSE All Share Index. The analysis captures the complex dynamics of market behaviour under inflationary pressure by looking at both symmetric and asymmetric long-run relationships between stock returns, inflation, interest rates, and investor sentiment. According to the Wald test, the results indicate that all sectors exhibit asymmetric long-run relationships, suggesting that changes in inflation, interest rates, and sentiment have varying effects on equity returns. In line with the Fisher hypothesis and the tax-augmented theory, industries like Consumer Discretionary, Consumer Staples, Financials, Industrials, Retail, Technology, and the JSE All-Share index as a whole serve as efficient inflation hedges during times of rising inflation. On the other hand, the market as a whole and the Basic Materials sector perform better during deflationary times, providing protection when inflation drops. However, the Healthcare industry responded significantly but negatively to both increasing and decreasing inflation, suggesting that it is ineffective as an inflation hedge in any scenario. Furthermore, there were insignificant inflation linkages in Consumer Services and Telecommunications. These results highlight the necessity of a state-contingent, sector-specific investment strategy that acknowledges the asymmetric nature of inflation's effect on equity returns in developing nations such as South Africa.